ANALYSIS OF THE USE OF PREPOSITIONS IN STUDENTS’ SCIENTIFIC ARTICLES EKASAKTI UNIVERSITY - Marisya, Susanti; Khairani, Zuraida (Jurnal Ilmu Pendidikan Ahlussunnah, 2024)
This research is motivated by a document review conducted related to several scientific articles of students. Based on this, it is known that the writing of scientific articles does not meet the standards of writing standard Indonesian. Some errors in the use of Indonesian Spelling, one of which is the placement of writing prepositions is not in accordance with standard Indonesian writing. Students consider that prepositions are not important to pay attention to so that students ignore writing in the use of prepositions. Several other studies have shown that the use of prepositions has not been mastered by elementary school students in writing narrative essays. This research was conducted by Ngaisah and Sugiarti in 2018. So, it can be concluded that prepositions have been taught starting from elementary school level. This research is a descriptive qualitative research. The data in this study are sentences that use prepositions in scientific articles written by students of Ekasakti University. The data source in this study is the scientific articles of students of Ekasakti University. The data collection technique in this study is the document search technique. The steps in data collection are: First, data is collected by selecting and collecting several scientific articles of students of Ekasakti University. Second, the author analyzes the use of prepositions in scientific articles of students. The findings and discussion show that students are still unable to use prepositions according to their function and writing. Students make several mistakes in writing single prepositions, namely in the use of the prepositions di and ke. Mistakes are also found in the use of combined prepositions that do not match their function, such as the use of the prepositions from…until.